Noninvasive Ventilatory Correction as an Adjunct to an Experimental Systemic Reperfusion Therapy in Acute Ischemic Stroke. (19th October 2010) - Barlinn, Kristian; Balucani, Clotilde; Palazzo, Paola; Zhao, Limin; Sisson, April; Alexandrov, Andrei V.
Abstract : Background . Obstructive sleep apnea (OSA) is a common condition in patients with acute ischemic stroke and associated with early clinical deterioration and poor functional outcome. However, noninvasive ventilatory correction is hardly considered as a complementary treatment option during the treatment phase of acute ischemic stroke. Summary of Case . A 55-year-old woman with an acute middle cerebral artery (MCA) occlusion received intravenous tissue plasminogen activator (tPA) and enrolled into a thrombolytic research study. During tPA infusion, she became drowsy, developed apnea episodes, desaturated and neurologically deteriorated without recanalization, re-occlusion or intracerebral hemorrhage. Urgent noninvasive ventilatory correction with biphasic positive airway pressure (BiPAP) reversed neurological fluctuation. Her MCA completely recanalized 24 hours later. Conclusions . Noninvasive ventilatory correction should be considered more aggressively as a complementary treatment option in selected acute stroke patients. Early initiation of BiPAP can stabilize cerebral hemodynamics and may unmask the true potential of other therapies.